Self-Efficacy and Quality of Life (QOL) in Women of Reproductive Age with Urinary Tract Infections (UTIs) - Sonia Karen Liz Sequera; Leena Kunnath Chacko (RGUHS Journal of Nursing Sciences)
Background Urinary tract infections UTIs are most frequently observed among women of reproductive age in both community and healthcare settings. About 50-60 of women suffer from UTIs at least once in their lifetime and one out of four suffer from recurrences. UTIs significantly affect a personrsquos quality of life QOL. Recurrent UTIs are a serious problem for women and pose challenges for healthcare providers.Objective To assess the self-efficacy and quality of life QOL of women with the aim of developing a nurseled prevention program.Methods A quantitative approach with a descriptive design was used. A purposive sampling method was used to recruit 120 women attending OPD of a selected hospital who tested positive for urine culture presented with UTI symptoms and were seeking treatment. Tools for data collection included the RAND SF-36 scale for QOL and a self-efficacy scale.Results The mean age of women was 27.76plusmn8.13 years. Recurrent infections were encountered in 73.4 women. Urine culture reports identified Escherichia coli in 85 cases and Klebsiella species in 15 cases as the causal organisms. Typical symptoms included painburning micturition 99.2 frequent urination 94.1 and urinary urgency 89.2. The quality of life of women in the physical domain and mental domains were 56.26plusmn17.64 and 57.21plusmn17.07 respectively. The self-efficacy of women with UTI was 28.13plusmn4.35. No correlation was found between self-efficacy and QOL. A significant association was found between the physical domain of QOL and the source of information received f4.820 P0.031 as well as between self-efficacy and the source of information on UTI f5.312 P 0.024.Conclusion A limited QOL and moderate self-efficacy were seen among women with UTIs affecting their daily life activities and well-being. This indicates the need to develop nurse-led preventive interventions for tackling urinary tract infections.